$572,000 Lowest Bid for Maritime School Dormitory - Vallejo Times-Herald (Vallejo Times-Herald)
Bids were opened in Sacramento yesterday by the State Division of Architecture for construction of a three-story dormitory to house 200 midshipmen at the California Maritime Academy.